Worldwide anaesthesia use during endovascular treatment for medium vessel occlusion stroke. Issue 4 (August 2022) - Kappelhof, Manon; Ospel, Johanna M; Cimflova, Petra; Kashani, Nima; Singh, Nishita; McDonough, Rosalie; Sehgal, Arshia; Almekhlafi, Mohammed A; Fiehler, Jens; Chen, Michael; Sakai, Nobuyuki; Majoie, Charles BLM; et al.
Introduction: The optimal anaesthesia approach for endovascular treatment (EVT) in acute ischaemic stroke is currently unknown. In stroke due to medium vessel occlusions (MeVO), the occluded vessels are particularly small and more difficult to access, especially in restless or uncooperative patients. In these patients, general anaesthesia (GA) may be preferred by physicians to prevent complications due to patient movement. We investigated physicians' approaches to anaesthesia during EVT for MeVO stroke. Methods: In a worldwide, case-based, online survey, physicians' preferred anaesthesia approach during EVT for MeVO stroke was categorized as "initial GA", "initial GA if necessary" (depending on patient cooperation), "no initial GA, but conversion if necessary" (start with local anaesthesia or conscious sedation), and "no GA". Preferred anaesthesia approaches were reported overall and stratified by physician and patient characteristics. Results: A total of 366 survey participants provided 1464 responses to 4 primary MeVO EVT case-scenarios. One-third of responses (489/1464 [33%]) favoured no initial GA, but conversion if necessary. Both initial GA and initial GA if necessary were preferred in 368/1464 (25%) of responses respectively. No GA was favoured in 244/1464 (17%). Occlusion location, respondent specialization (interventional neuroradiology), higher age, and female respondent sex were significantly associated with GA preference. GA was more often used in Europe than in other parts of the world ( p  < 0.001). Conclusions: Anaesthesia approaches in MeVO EVT vary across world regions and patient and physician factors. Most physicians in this survey preferred to start with local anaesthesia or conscious sedation and convert to GA if necessary.